2022
DOI: 10.1029/2021tc007110
|View full text |Cite
|
Sign up to set email alerts
|

Active Tectonics of the North Tunisian Continental Margin

Abstract: A poorly defined boundary between the Nubia and Eurasian plates runs along the Northern Tunisian continental margin. The Tunisia margin is deformed by a slow NW–SE trending convergence resulting in a diffuse deformation zone with scarce and scattered seismicity compared to the seismic activity into the neighboring regions to the east and west along the boundary. The area has been poorly studied and therefore its recent evolution is almost unknown, particularly offshore. Here, we present a structural analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In Mediterranean subduction-related basins, contraction of young volcanic basement, formed in an extensional context with limited faulting, occurred during an abrupt change from Miocene extension to convergence in lattermost Miocene and Pliocene (Camafort et al, 2020;Gómez de la Peña et al, 2021), and it is currently accumulating most deformation in the region (Gómez de la Peña et al, 2022). Reactivation of pre-existing tectonic features resulted in local inversion and formation of related anticline-syncline folds (Camafort et al, 2022;Giaconia et al, 2015;Zitellini et al, 2020), resembling deformation observed in the NW Sulu Sea (Figure 2, line SO23-01, CDPs 8000-5900; Figure 6, line SO23-16, CDPs 6500-4000).…”
Section: Contractional Reactivation Of the Segmented Nw Sulu Seamentioning
confidence: 99%
“…In Mediterranean subduction-related basins, contraction of young volcanic basement, formed in an extensional context with limited faulting, occurred during an abrupt change from Miocene extension to convergence in lattermost Miocene and Pliocene (Camafort et al, 2020;Gómez de la Peña et al, 2021), and it is currently accumulating most deformation in the region (Gómez de la Peña et al, 2022). Reactivation of pre-existing tectonic features resulted in local inversion and formation of related anticline-syncline folds (Camafort et al, 2022;Giaconia et al, 2015;Zitellini et al, 2020), resembling deformation observed in the NW Sulu Sea (Figure 2, line SO23-01, CDPs 8000-5900; Figure 6, line SO23-16, CDPs 6500-4000).…”
Section: Contractional Reactivation Of the Segmented Nw Sulu Seamentioning
confidence: 99%